(untitled) (Altre Modernità, 2012)
The aim of this lecture is to explore the question of representing terrorists in Israeli literature, namely in the books, Ha-me’ahev, (The Lover), by A.B. Yehoshua, Ha-Qaytanah Shel Kneller (Kneller Happy Camp) by Etgar Keret, Shum gemadim lo yavo’u (The King of Falafel) by Sarah Shilo and Tanin pigua (Croc attack) by Assaf Gavron. A particular attention will be devoted to the confrontation with the other and its purpose in these books.